IMPACT OF TAX AGGRESSIVENESS ON THE FINANCIAL PERFORMANCE OF LISTED INSURANCE FIRMS IN NIGERIA - Daniel Terna, Kwahar; Ene, Emeka; Ene, Josephine (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2025)
This study examines the impact of tax aggressiveness on the financial performance of quoted insurance companies in Nigeria, examining the research problem surrounding how various tax planning techniques affect the profitability of a firm. This study used a holistic analysis approach of descriptive statistics to get an overview of the data distribution to correlation analysis to analyse the relationship between variables. The necessity of robust econometric techniques was confirmed by applying the Cross-Section Dependence (CD) test to test cross-sectional dependence. Thus, the Difference GMM estimator was used to overcome issues related endogenous and serial correlation to provide valid estimates. The findings revealed that Effective Tax Rate (ETR) was negatively but significantly related to financial performance showing that higher tax burden weakens profitability. This finding agrees with the existing literature, which indicates that high taxes inhibit the reinvestment of capital. This lent to the idea that highfaluting tax plans could minimise taxes, thereby maximally increasing profits. Non-Debt Tax Shield (NDTS) had a positive and significant impact on financial performance, indicating that strategic utilization of tax shields (depreciation and amortization) brought better financial condition. These findings led to specific recommendations. One of the recommendations was for policymakers like the Federal Inland Revenue Service (FIRS) and the National Insurance Commission (NAICOM) to formulate tax policies that reduce the tax burden of insurance companies. The guidelines also suggested ethical tax practices by companies and better management of deferred tax liabilities. It was also advised to constructively use non-debt tax shields to boost profits.